Effect of Heartfulness Meditation on Vital Parameters among Experienced and New Meditators - Shaik Yasmeen; Pavan Kumari J; Rapuri Sowmya Pallavi; Sunita Sreegiri; M.N.S.Vaishnavi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Meditation has been key component of Eastern spiritual practices. Heartfulness meditation is a unique heart based system with key practices like cleaning and meditation aided by yogic transmission. Meditation includes a state of deep relaxation and calmness due to changes produced in pertinent areas of brain which improves the performance of brain and circulatory system. Objectives: To analyze and compare the effect of 30-minute heartfulness meditation session on vital parameters of experienced and new meditators. Methods: An observational study was conducted for a period of 1 month among experienced and new meditators at Heartfulness Training Center, Tirupati with an estimated sample size of 45 in each group (N=90). All the participants were selected by simple random sampling and were subjected for personal interview by using semi structured questionnaire. Anthropometric measurements and vital parameters like pulse rate, blood pressure were recorded. The difference between means was analyzed by using paired and unpaired t-test. Results: Mean age of study participants was 56.7±13. Mean heart rate among experienced meditators was decreased from 82.0±8.8 to 80.3±9.9. The mean systolic blood pressure among experienced meditators and new meditators after meditation was found to be 128.1±17.2 and 121.5±12.8 respectively. Statistically significant difference was found in systolic blood pressure levels among both the groups. Conclusion: Heartfulness meditation session was found to have favourable effect on vital parameters especially systolic blood pressure.